Samurai Accountant: A Theory of Auditing and Plunder - Border, Kim C.; Sobel, Joel (Review of Economic Studies, 1987)
A risk neutral principal wishes to exact a payment from a risk neutral agent whose wealth he does not know, but may verify through a costly auditing procedure. We characterize efficient schemes for the principal when he is allowed to choose schedules for preaudit and postaudit payments and audit probabilities, subject to the constraint that only monetary incentives can be used and that the principal may never make a net payment to the agent. The main results are that efficient schemes involve preaudit payments which are increasing in the agent's wealth, audit probabilities are decreasing in the agent's wealth and also satisfy certain constraints as equalities. In general, such schemes involve stochastic auditing and rebates after an audit.